Complex lava tube networks developed within the 1792–93 lava flow field on Mount Etna (Italy): insights for hazard assessment - Calvari, S.; Giudice, G.; Maugeri, R.; Messina, D.; Morgavi, D.; Miraglia, L.; La Spina, A.; Spampinato, L. (Frontiers in Earth Science, 2024)
Lava tubes are powerful heat insulators, allowing lava to practically keep the initial temperature and travel longer distances than when freely flowing on the ground surface. It is thus extremely important to recognize how, when and where these structures form within a lava flow field for hazard assessment purposes, in order to plan possible interventions should a lava flow approach inhabited areas. Often being formed within thick and complex lava flow fields, lava tubes are difficult to detect, study and explore. In this study, we analyse the 1792–93 Etna lava flow field emplaced on a steep slope (>4°) which comprises several lava tubes located at different distances from the eruptive fissure, at different levels within the lava flow field, and showing various inner morphologies, with peculiar inner features related to their maturity and eruptive history. Our aim is to verify whether it is possible to connect the underground features with features observed on the lava flow surface in order to reconstruct the extension of the tube network and unravel the genetic processes. Our results show that, in the studied lava flow field, a clear correspondence is possible between shallow tubes emplaced late during the lava flow field growth and surface textures. In addition, vertical and horizontal tube capture is very widespread, and might be the primary process for lava tube persistence and long life. Our results might be applicable to other lava tubes on Earth and other rocky planets.